2017
DOI: 10.18632/oncotarget.19905
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin receptor agonists inhibit leptin induced pSTAT3 and in vivo pancreatic tumor growth

Abstract: Obesity is a significant risk factor for pancreatic cancer, harboring a chronic inflammatory condition characterized by dysregulation of the adipokines, leptin and adiponectin, that in turn alter oncogenic signaling pathways. We and others have shown that leptin promotes the proliferation and an invasive potential of pancreatic cancer cells through STAT3 mediated signaling. However, the role of adiponectin on the tumorigenicity of pancreatic cancer has not been elucidated. Adiponectin represents an important n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 49 publications
1
64
0
Order By: Relevance
“…Recently, the rst oral adiponectin receptor agonist AdipoRon has been identi ed, but its potential pharmacological usage has marginally been explored [22][23][24]. In this regard, initial evidence candidates AdipoR as a potential antineoplastic molecule in various preclinical models, including pancreatic and ovarian cancer [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the rst oral adiponectin receptor agonist AdipoRon has been identi ed, but its potential pharmacological usage has marginally been explored [22][23][24]. In this regard, initial evidence candidates AdipoR as a potential antineoplastic molecule in various preclinical models, including pancreatic and ovarian cancer [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, not completely exhaustive and partially controversial data are available concerning the relationship between AdipoRinduced cell death and apoptosis initiation. Messaggio et al reported that AdipoR increases apoptotic positive cells in human and mouse pancreatic cancer [29], whereas Akimoto et al demonstrate that AdipoR-treated MIA PaCa-2 cells die largely via RIPK1-dependent necroptosis and mitochondrial dysfunction-mediated autophagy [28]. e mechanistic target of rapamycin (mTOR) is a pivotal prosurvival signaling pathway that negatively affects autophagy and self-digesting independent cell death processes [41,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AdipoRON effectively improved insulin sensitivity and restored glucose homeostasis via the activation of AdipoR1-AMPK-PGC1α and AdipoR2-PPARα signaling pathways (162). AdipoRON treatment also mimicked adiponectin's established anti-diabetic effects (163) and ability to enhance cellular capacity for mitigating oxidative-stress (162,164), enhancing lipid/glucose oxidation in mitochondria (162,164), anti-inflammatory responses (162,(164)(165)(166)(167), lifeprolonging effect (162,163), anti-cancer effects (168,169), procell survival and anti-apoptotic effect (170,171), neuronal- (172,173), reno- (174,175), and cardio-/vascular-protective effects (165,(176)(177)(178)(179). However, exciting AdipoRON research in animal models has not been translated to establishment of a drug for human use and the search continues for additional small molecule AdipoR agonists which have little or no toxicity.…”
Section: Adiporonmentioning
confidence: 99%